Prevalansi Cedera Ektremitas Atas pada Permainan Softball - Ade Tuti Lestari; Bachtiar Bachtiar; One Lailla Trisanti; Ida Zubaid (Jendela Olahraga, 2021)
Many athletes don’t understand the risk factors for injury, so they have less awareness, acute and chronic due internal and external. This study is aimed to determine the prevalence of injuries in the throw technique. The method used descriptive with a survey technique using a questionnaire. The results was prevalence of injuries from throwers, under hand toss3, side hand throw 8, and over hand throw 19. From the aspect of  have been injured 15, handling injuries 20, and throwing techniques 14. Forover hand throw 19, side hand throw 8 and under hand toss 3. For over hand throw 19, side hand throw 8 and under hand toss 3. The relationship between throw and injury was 10 from over hand throw, 6 from side hand throw, and 3 from under hand toss. Based on observations from the position of the injury, were deltoid 15, biceps 8, triceps 5, and wrist 2. Based on the relationship between throw and the position of the injuries, 13deltoid, 4 biceps and 2 triceps injuries from over hand throw, side hand throw 4, experienced biceps injuries, 2 deltoid, 2 triceps, and 2 under hand toss, 2 wrist  and 1 triceps. Keywords: Prevalence, Injury, SoftballAbstrakBanyak atlet kurang memahami factor resiko terjadinya cedera selama melakukan olahraga sehingga kurang menyadari telah mengalami cedera, baik akut maupun kronis yang diakibatkan factor internal dan eksternal.Sehingga penelitian ini bertujuan untuk mengetahui prevalensi cedera ekstremitas atas pada teknik lemparan.Metode yang digunakan deskriptif dengan teknik survei menggunakan angket. Hasil penelitian: Prevalensi cedera dari pelempar, under hand toss 3 orang, side hand throw 8 orang, dan over hand throw 19 orang. Dari aspek pernah atau sedang mengalami cedera 15 orang, cara penanganan cedera 20 orang, dan teknik lemparan 14 orang. Untuk jenis lemparan over hand throw 19 orang, side hand throw 8 orang dan under hand toss 3 orang. Hubungan jenis lemparan terhadap cedera, lemparan over hand throw 10 orang, side hand throw 6 orang, dan under hand toss 3 orang. Berdasarkan pengamatan letak cederanya deltoid 15 orang, biceps 8 orang, triceps 5 orang, dan  wrish 2 orang. Berdasarkan hubungan jenis lemparan dan letak cederanya 13 orang cedera deltoid, 4 orang cedera biceps dan 2 orang cedera triceps dari over hand throw, side hand throw 4 orang cedera biceps, 2 orang cedera deltoid, 2 orang cedera triceps, dan under hand toss 2 orang cedera wrish dan 1 orang cedera triceps. Kata Kunci: Prevalensi, Cedera, Softball